Blood Levels of Monoamine Precursors and Smoking in Patients with Schizophrenia - Mathai, Ashwin Jacob; Kanwar, Jyoti; Okusaga, Olaoluwa; Fuchs, Dietmar; Lowry, Christopher A.; Peng, Xiaoqing; Giegling, Ina; Hartmann, Annette M.; Konte, Bettina; Friedl, Marion; Gragnoli, Claudia; Reeves, Gloria M.; et al. (Frontiers in Public Health, 2016)
Smoking is highly prevalent in patients with schizophrenia and exerts a negative impact on cardiovascular mortality in these patients. Smoking has complex interactions with monoamine metabolism through the ability of cigarette smoke to suppress Type 1 T helper cell (Th1) type immunity, the immunophenotype that is implicated in phenylalanine hydroxylase (PAH) dysfunction and tryptophan breakdown to kynurenine via indoleamine 2,3-dioxygenase (IDO). Nicotine also induces tyrosine hydroxylase gene (TH) expression, leading to increased synthesis of catecholamines. Furthermore, there is evidence for PAH dysfunction in schizophrenia. This study aimed to compare the plasma levels of selected monoamine precursors and their metabolites in smokers vs non-smokers in a large sample of patients with schizophrenia. We measured plasma phenylalanine, tyrosine, tryptophan and kynurenine levels using high-performance liquid chromatography (HPLC) and calculated phenylalanine: tyrosine (Phe: Tyr) and kynurenine: tryptophan (Kyn: Trp) ratios in 920 patients with schizophrenia. Analysis of variance (ANOVA) and linear regression analyses were used to compare these endpoints between 3 groups of patients with schizophrenia; 1) current smokers, 2) past smokers and 3) non-smokers. There were significant differences among the three groups with regards to tyrosine levels [F(2,789)=3.77, p=0.02], with current smokers having lower tyrosine levels when compared to non-smokers (p=0.02). Kynurenine levels and Kyn :Trp ratio were different among the 3 groups [F (2,738)=3.17, p=0.04, F(2,738)=3.61, p=0.03] with current smokers having lower kynurenine levels (p=0.04) and higher Kyn: Trp ratio (p=0.02) when compared to past smokers. These findings need to be replicated with protocols that include healthy controls to further elucidate the neurobiological underpinnings of altered tyrosine and kynurenine levels in smokers. Results do suggest potential molecular links between schizophrenia and smoking that may represent biomarkers and treatment targets for reducing an important modifiable cause of general morbidity and mortality in patients with schizophrenia.